Hubungan Antara Manajemen Waktu Dengan Regulasi Diri Pada Siswa Atlet di SMAN 8 Kota Bekasi - Zahro, Nur Rahmania; Muzzamil, Ferdy (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine whether or not there is a relationship between Time Management and Self-Regulation in Student Athletes at SMAN 8 Bekasi City. The various demands received by student athletes can require them to have good time management skills and good self-regulation in order to meet the demands and achieve the achievements they dream of. The research method used in this research is a quantitative method, with a total of 123 student athletes as respondents. The assumption test used in this research is the normality test with a significance of 0.200 (p>0.05) which means the data is normally distributed, the linearity test with a significance of 0.219 (p>0.05) which means there is a linear relationship, and the homogeneity test with significance 0.510 (p>0.05) means the data is homogeneous. The results of this research obtained a correlation coefficient value of 0.529 with a significance level of 0.000 (p<0.05), which means there is a relationship between Time Management and Self-Regulation in student athletes at SMAN 8 Bekasi City and there is a positive relationship.